Risk factors for prolonged surgical duration of tracheobronchial foreign body removal in children: a single-center retrospective study - Su, Zhe; Zhang, Jianmin; Gao, Zhengzheng; Wang, Fang; Li, Lijing; Xu, Zenghua; Liu, Heqi; Zhang, Fuzhou (Frontiers in Pediatrics, 2025)
ObjectThis study aims to analyze the clinical characteristics of children with tracheobronchial foreign body and to investigate the factors influencing the surgical duration of rigid bronchoscopic foreign body removal under general anesthesia.MethodsWe retrospectively identified 421 children diagnosed with tracheobronchial foreign body undergoing rigid bronchoscopy between January 2020 and December 2021. A comprehensive analysis was conducted on patient demographics, including age, weight, gender, American Society of Anesthesiologists (ASA) physical status classification, foreign body type and location, duration of foreign body retention, preoperative symptoms, signs, imaging findings, tracheobronchial manifestations observed during bronchoscopy, and surgical durations. Statistical analysis utilized both univariate and multivariate linear regression models to assess factors influencing the surgical duration of tracheobronchial foreign body removal in children.ResultsThe mean age of children with tracheobronchial foreign body was 1.59 years (1.32, 2.04). The male-to-female ratio was 1.8:1, and the ASA physical status classification was predominantly ASA II (96.7%). Organic foreign body accounted for 94.8% of cases, with 91.7% located unilaterally. Univariate and multivariate linear regression analyses revealed that ASA III, pulmonary rales, and the presence of one, two, or three specific tracheobronchial manifestations observed during bronchoscopy—including mucosal hyperemia and edema, purulent exudate, and granulation tissue—were independent risk factors associated with prolonged surgical duration for foreign body removal (P < 0.05).ConclusionASA III, pulmonary rales, and various tracheobronchial manifestations observed during bronchoscopy are significant risk factors associated with prolonged surgical duration for foreign body removal in children.